2015
DOI: 10.20344/amp.5941
|View full text |Cite
|
Sign up to set email alerts
|

Um Caso Raro de Dentes Neonatais

Abstract: RESUMOOs dentes neonatais correspondem a um distúrbio raro da erupção dentária, surgindo na cavidade oral no primeiro mês de vida, habitualmente na região anterior da mandíbula, sendo a sua etiologia desconhecida. Podem motivar dificuldades na amamentação e ser alvo de aspiração ou deglutição. Descreve-se o caso de um recém-nascido prematuro que no segundo dia de vida apresentava edema, hiperemia gengival e uma pequena tumefação na região dos incisivos centrais inferiores. Dez dias depois, foram detetados, nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…If the tooth presents good implantation and is part of the normal primary dentition, the first treatment of choice will be the maintenance of the tooth in the oral cavity, as long as it does not cause harm to the child 4 , as reported in the first clinical case. However, if it is interfering with breastfeeding or presenting great mobility, with risk of displacement and aspiration, the tooth must be removed 3,4,11 , as in the second clinical case. Although some authors report the possibility of aspiration of these teeth, there are no reports in the literature confirming this occurrence 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the tooth presents good implantation and is part of the normal primary dentition, the first treatment of choice will be the maintenance of the tooth in the oral cavity, as long as it does not cause harm to the child 4 , as reported in the first clinical case. However, if it is interfering with breastfeeding or presenting great mobility, with risk of displacement and aspiration, the tooth must be removed 3,4,11 , as in the second clinical case. Although some authors report the possibility of aspiration of these teeth, there are no reports in the literature confirming this occurrence 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the clinical point of view, there was no doubt about the diagnosis and the therapeutic approach, thus avoiding to subject babies to unnecessary radiation 17 . Still, due to the small opening of the mouth and the lack of cooperation inherent to babies' age [18][19][20] , the radiographic procedure would be very uncomfortable, adding small benefits to the case.…”
Section: Clinical Case Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An extreme treatment would involve the extraction of the natal tooth, which is recommended in the case of a supernumerary tooth, when associated with Riga-Fede syndrome or if is there is excess mobility without bone insertion 12,22 . The concern over excess mobility resulting from insufficient root development stems from the fact that this tooth may constitute a risk to the airways due to the possibility of aspiration 13,23 . However, this risk, in truth, is unlikely, as no reports exist of an actual occurrence of aspiration 24 .…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the HUCAM patient records, conducted subsequently, confirmed the information supplied by the mother. Despite the existence of this relationship between prematurity and the delay in eruption of the first deciduous tooth, cases have been reported in the literature of preterm newborns that have natal or neonatal teeth [9][10][11][12][13] . In a retrospective study of 17,000 children, between 1984 and 2001, the presence of natal teeth was observed in just five newborns, of which two were preterm 14 .…”
Section: Introductionmentioning
confidence: 99%